Synthesis, Photophysical and Electrochemical Studies on Peripherally Ruthenated Tetraphenylporphyrin - Tamijselvy, S. (Asian Journal of Chemistry, 2017)
Ruthenium(II) complexes of 5-(4-hydroxyphenyl)-10,15,20-tris-(4-methylphenyl)porphyrin and 5,10,15,20-tetrakis(4-hydroxyphenyl)-porphyrin have been synthesized in basic medium and spectroscopically characterized. The complexes show broad bands in the visible region due to overlap of porphyrin transitions with the metal-to-ligand charge transfer (MLCT) transitions arising from cis-Ru(bipy)2Cl2. 1H NMR indicates p-electron interactions between the porphyrin ring and bipyridyl rings. The complexes are emissive both at room temperature and at 77 K with two independent emissions at 77 K, one from the excited state of the porphyrin moiety at 650 and 720 nm and the other from the excited state of the ruthenium moiety at 700 nm. No excited state intramolecular energy transfer reactions have been detected. However the quantum yield of the complexes is reduced due to heavy atom effect. Time resolved fluorescence decay analyses show dual life time at 1.5 and 7.7 ns in dichloromethane. The shorter life time is assigned to singlet-excited state of ruthenium and longer life time to porphyrin singlet excited state. Electrochemical analysis of these species in dichloromethane exhibits three anodic peaks at around 0.68, 0.98 and 1.42 V versus SCE, analogous to the Ru3+/2+ couple and two successive one-electron oxidation processes on the porphyrin ring, respectively. On the other hand, cathodic potentials at around -0.8, -1.4 and -1.54 V versus SCE, with first two peaks corresponding to two successive reduction taking place at the porphyrin ring and the third peak corresponding to reduction of bipyridyl unit. All spectroscopic studies reveal perturbation on the electronic levels of both porphyrin ring and ruthenium chromophore.